Grains of sand - Delacroix, Sibylle; Li, Karen (Toronto, Ontario : Owlkids Books, 2018)
"On the last day of a family vacation, a little girl is as blue as the sea, and her shoes are filled with sand. What should she do with all of this sand? Together, she and her brother decide to plant the grains of sand, and imagine what will grow. A field of beach umbrellas, to wave hello to the sun? Or a forest of windmills, to fill the sails of a boat? Before drifting off to sleep, the girl has her dad promise they'll go back for new grains of sand next year. Spare text will prompt readers to wonder and imagine their own possibilities, while illustrations in a palette of yellows and grays convey the sun-soaked joy and the lingering nostalgia of family vacations well remembered."--
Translation of: Graines de sable.